Plasmablastic Lymphoma: A Review of Current Knowledge and Future Directions - Ghaleb Elyamany; Eman Al Mussaed; Ali Matar Alzahrani (Advances in Hematology)
Plasmablastic lymphoma (PBL) is an aggressive subtype of non-Hodgkin’s lymphoma (NHL), which frequently arises in the oral cavity of human immunodeficiency virus (HIV) infected patients. PBL shows diffuse proliferation of large neoplastic cells resembling B-immunoblasts/plasmablasts, or with plasmacytic features and an immunophenotype of plasma cells. PBL remains a diagnostic challenge due to its peculiar morphology and an immunohistochemical profile similar to plasma cell myeloma (PCM). PBL is also a therapeutic challenge with a clinical course characterized by a high rate of relapse and death. There is no standard chemotherapy protocol for treatment of PBL. Cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) or CHOP-like regimens have been the backbone while more intensive regimens such as cyclophosphamide, vincristine, doxorubicin, high-dose methotrexate/ifosfamide, etoposide, high-dose cytarabine (CODOX-M/IVAC), or dose-adjusted etoposide, prednisone, vincristine, cyclophosphamide, and doxorubicin (DA-EPOCH) are possible options. Recently, a few studies have reported the potential value of the proteasome inhibitor bortezomib and thalidomide in PBL patients. The introduction of genes encoding artificial receptors called chimeric antigen receptors (CARs) and CAR-modified T cells targeted to the B cell-specific CD19 antigen have demonstrated promising results in multiple early clinical trials. The aim of this paper is to review the recent advances in epidemiology; pathophysiology; clinical, pathologic, and molecular characteristics; therapy; and outcome in patients with PBL.